Rekomendasi Penentuan Kelas Unggulan Menggunakan Metode Complex Proportional Assessment Dan Step-wise Weight Assessment Ratio Analysis - A. Ferico Octaviansyah Pasaribu; Donaya Pasha (Swarnadwipa, 2024)
Class of Excellence is an educational program designed to provide superior educational services and oriented towards academic achievement and overall development of student potential. Featured class determination recommendations is a process that considers a variety of factors to determine which students meet the criteria for admission into the program. The purpose of this study can provide a recommendation to the school in determining students who enter superior classes based on the criteria used by applying the Complex Proportional Assessment (COPRAS) method and the Step-wise Weight Assessment Ratio Analysis (SWARA) weighting method. The SWARA method is an analytical approach used in multi-criteria decision making to determine the relative weight of each criterion. The COPRAS method is an analytical approach used for multi-criteria decision making, especially in the context of complex evaluation of alternatives. The ranking results show a list of excellent class students as many as 21 students based on the highest scores from 1 to 21 students. This result becomes a recommendation to the school in determining excellent class students.